Natural resources: an alternative used as a complementary therapy by people who live with virus/immune-deficiency acquired syndrome. Tampico Tamaulipas. Mexico. - Martinez SP; Gonzalez JS; Attias IL (Cultura de los Cuidados, 2009)
Aims: Were centred in understanding and explaining the meaning of natural resources for those people living with AIDS, from the perspective of anthropology of care, at the same time to determine which are those resources and their effectiveness from the users' perspective and to know how they apprehend those natural resources, who recommend them, as well as their influence in per-severing with traditional medicine. Also to request opinions about such natural resources among their own traditional medical doctors. Methodology: A qualitative descriptive study was performed by means of action investigation type based on an ethnographic method. The sample was constituted by 1263 individuals living with the virus or AIDS, registered cases within the Jurisdiccion Sanitaria II in Tampico (Mexico) (CONASIDA -2002), from whom 180 form a self- aid group fully coordinated with the Frente Nacional de Personas Afectadas de Virus de SIDA. (FRENPAVIH-2004). 14 individuals were selected as key informants in a convenient sample. Doctors opinions were considered due to their paramount knowledge with respect to the matter, their selection done at random but for their premise of being directly involved in AIDS patients. Results: 39 different types of vegetables (medical plants, fruits and greens). No specifically taken into consideration for the treatment were some mineral or animal resources. The AIDS people declare having used some green resources, as from their personal point of view they have experienced an improvement in their health, they feel better . They buy them locally (natural resources shops, herbal shops or are cultivated in their own gar-dens). They have been recommended by people of their own environment, their social group, their family or got them from the self-aid group where they belong to. Doctors participant in the study express that natural resources as an alternative or complement to traditional medical treatment to AIDS are not scientific but they confess not to be familiarized with those medical plants o alternative medicine. Conclusions: According to testimonials the conclusion is that there is evidence that within these type of groups their common habits and health beliefs are present in their lives thus the use of natural resources in AIDS patients go parallel to the traditional medical treatments and together with their own values and way of life, social environment where they belong to what allows them to have their personal cosmos-vision idea.